Therapeutic Angiogenesis: Recent and Future Prospects of Gene Therapy in Peripheral Artery Disease - Tanaka, Michiko; Taketomi, Kikuko; Yonemitsu, Yoshikazu (Current Gene Therapy, 2014)
Peripheral artery disease (PAD) is a highly prevalent disease, which still has unmet medical needs. Therapeutic angiogenesis for PAD, achieved by gene therapy, has achieved promising results in preclinical studies and early-phase clinical trials, yet few late-phase clinical trials have been conducted or have not shown efficacy. This article provides an overview of the progression of angiogenesis research in gene therapy field as it applies to PAD. The focus of angiogenic growth factors and clinical trials is introduced as a frontier of therapeutic angiogenesis. The article also includes insights into future directions from bench to bedside.
Keywords: plasmid